Superencryption of BASE 64 Algorithm and ELGAMAL Algorithm on Android Based Image Security - Usman Gumanti; A M H Pardede; Husnul Khair (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2023)
In the current era of globalization, the development of information technology is growing rapidly, there is a possibility that there will be data leaks when the process of exchanging information is carried out, then security becomes a very important aspect which will cause unwanted things, for example manipulation of images in the form of information systems. If this important information falls into the hands of the wrong person, it can be negative and can be detrimental to the image owner. So a security system is designed that functions to protect the data that is sent while maintaining its authenticity and authenticity. Various ways have been developed for data security, one of which is by using cryptography. Cryptography is the science of securing data by using data transformation so that the resulting data cannot be understood by other parties. This transformation can provide a solution to two data security problems, namely the problem of privacy and data authentication. Cryptographic techniques can be used to ensure data security, one of which can be utilized is encryption and description of data or in other words encoding data so that only the person concerned can understand the contents of the data. The proper use of information technology is very important to send private and confidential images to certain parties. These images are still in the form of PNG and JPG extensions, for this reason a security system is needed that can protect images that are transmitted through a communication network, one way that can be done to secure images is using the BASE 64 algorithm and the ELGAMAL algorithm.